Animal source food beliefs, perceptions, and dietary intake among mothers and children in Kenya informal settlements - Boncyk, M.; Hunter, E.N.; Blake, C.E.; Prieto-Merino, D.; Lepine, A.; Bukachi, S.A.; Ngutu, M.; Kadiyala, S.; Domínguez Salas, Paula (2024)
Objectives: To explore how beliefs and perceptions about animal-source foods (ASFs) influence mother and child dietary intake in Nairobi, Kenya.